Electrochemical Detection of Serum Antibodies Against Mycobacterium avium Subspecies paratuberculosis - Hatate, Kaoru; Rice, J. Hunter; Parker, Karsten; Wu, J. Jayne; Turner, Amy; Stabel, Judith R.; Eda, Shigetoshi (Frontiers in Veterinary Science, 2021)
Mycobacterium avium subsp. paratuberculosis (MAP) causes a chronic inflammatory intestinal disease, called Johne's disease (JD) in many ruminants. In the dairy industry, JD is responsible for significant economic losses due to decreased milk production and premature culling of infected animals. Test-and-cull strategy in conjunction with risk management is currently recommended for JD control in dairy herds. However, current diagnostic tests are labor-intensive, time-consuming, and/or too difficult to operate on site. In this study, we developed a new method for the detection of anti-M. paratuberculosis antibodies from sera of M. paratuberculosis-infected animals. M. paratuberculosis antigen-coated magnetic beads were sequentially reacted with bovine serum followed by a horseradish peroxidase (HRP)-labeled secondary antibody. The reaction of HRP with its substrate was then quantitatively measured electrochemically using a redox-active probe, ferrocyanide. After optimization of electrochemical conditions and concentration of the redox-active probe, we showed that the new electrochemical detection method could distinguish samples of M. paratuberculosis-infected cattle from those of uninfected cattle with greater separation between the two groups of samples when compared with a conventional colorimetric testing method. Since electrochemical detection can be conducted with an inexpensive, battery-operated portable device, this new method may form a basis for the development of an on-site diagnostic system for JD.